Development of a course and training information system for non-formal education providers - Kisworo, Bagus; Prasojo, Lantip Diat; Sujarwo, Sujarwo (Edelweiss Applied Science and Technology, 2026)
This research aims to: (1) develop a course and training information system design that incorporates Supply Chain Management (SCM) and Decision Support System (DSS) concepts, called sikapin.id; (2) assess the feasibility of the developed system; (3) evaluate the practicality of the system for users; and (4) measure the effectiveness of the system for non-formal education providers in Semarang City. The study employs a Research and Development (R&D) approach based on Borg and Gall’s steps. A limited trial involved 30 respondents, while a larger trial included 243 respondents. The findings indicate that: (1) The sikapin.id system was successfully designed with integrated SCM and DSS features; (2) The system’s feasibility is rated as very feasible, with design experts and media experts both assessing it at 87.5%, and practitioners at 94.1%; (3) The system’s practicality is high, with prospective participants rating it an average of 3.44 and organizers rating it 3.64, indicating very practical; and (4) The system proved effective, demonstrated by a significant increase in test scores from an average of 49.49 pretest to 59.30 posttest, with a significance value of 0.000, which is less than 0.05.